1992
DOI: 10.1021/bc00018a009
|View full text |Cite
|
Sign up to set email alerts
|

Acidic derivatives of homocysteine thiolactone: utility as anionic linkers

Abstract: Homocysteine thiolactone (2) derivatives in which the nitrogen is acylated with groups containing acidic functionalities have been synthesized. These include the succinyl (3), the carboxymethylglutaryl (4), the 3-phosphonopropionyl (7), and the 3-sulfopropionyl (8) derivatives. These thiolactones can be used to introduce a thiol functionality into proteins such as the outer membrane protein complex of Neisseria meningitidis (OMPC) allowing conjugation with electrophilic ligands. This chemistry is the same as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Maleimide equivalents in an aliquot of the activated Pfs25H were measured with an N-acetylcysteine consumption assay using Ellman's reagent, 5,5Ј-dithionitrobenzoic acid (Pierce) to measure residual thiol (19). N-acetylhomocysteine thiolactone-activated OMPC was aseptically prepared with a 2-h aging time as described (20), except that potassium phosphate buffer was replaced with sterile water. Before use, Nacetylhomocysteinyl-OMPC was made to be 25 mM 2-morpholinoethane sulfonic acid buffer, pH 6.1.…”
Section: Methodsmentioning
confidence: 99%
“…Maleimide equivalents in an aliquot of the activated Pfs25H were measured with an N-acetylcysteine consumption assay using Ellman's reagent, 5,5Ј-dithionitrobenzoic acid (Pierce) to measure residual thiol (19). N-acetylhomocysteine thiolactone-activated OMPC was aseptically prepared with a 2-h aging time as described (20), except that potassium phosphate buffer was replaced with sterile water. Before use, Nacetylhomocysteinyl-OMPC was made to be 25 mM 2-morpholinoethane sulfonic acid buffer, pH 6.1.…”
Section: Methodsmentioning
confidence: 99%
“…In 1956 it was found that N-acetyl-Hcy-thiolactone can react with amines and amino acids in alkaline solutions (pH > 9) with the formation of a peptide bond [203]. Nevertheless, N-acetyl-Hcy-thiolactone has been used to introduce a thiol functionality into small molecules and macromolecules, including aminoglycosides, amino lipids, muramyl dipeptide, cell-surface carbohydrates, human serum albumin, lactoglobulin, enzymes, and oligonucleotides for a variety of applications [207]. However, because N-acetyl-Hcy-thiolactone is much less reactive than Hcy-thiolactone, these studies required long reaction times, relatively high pH [205], or the presence of silver ions as a catalyst [205,206].…”
Section: Reactivity Toward Amino Groupsmentioning
confidence: 99%
“…a carrier protein that has been shown to be effective (27) in humans as a conjugate with H. influenzae capsular polysaccharide (PedvaxHIB @). Conjugation of thiolated OMPC with bromoacetyl-Arg-Arg-Arg produced an insoluble product (28), whereas neutral peptide-OMPC conjugates were soluble entities. Assay of the unique thioether in conjugate hydolysates provides a convenient means of determining the degree of covalent attachment of the two macromolecules.…”
Section: Vaccine Conjugationmentioning
confidence: 99%